La religion de Madame Riccoboni dans sa correspondance - Marie–Pierre Legrand (L'Atelier du CRH)
Daughter of a man judged for bigamy, hidden in a convent as illegitimate child, then comedian when Church excommunicated comedians, Mme Riccoboni was an acquaintance of Marivaux and Luigi Riccoboni’s daughter in law and on the other hand, she was attending the d’Holbach’s salon, nest of atheists.